Japan in Cuba. The phenomenon of manga and other spaces for cooperation in cultural topics - Fabeloc, Sunamis (Mirai. Estudios Japoneses, 2021)
At present the Japanese cultural influence in Cuba is notably significant. This has been a growing process that has evolved at several moments in time, and at different levels and spheres, but that has without any doubt brought both its people closer together. The influence of Japanese manga, which is among the great comic book traditions worldwide, can be highlighted. In the Caribbean island, among the new generations, the emergence of a group of creators and fans of Japanese culture can be identified. These creators have empirically incorporated this imprint into their productions and, therefore, demand spaces for meeting and cultural exchange. In this light, the feasibility of exploring new areas of cooperation and common interest, as well as enhancing existing ones, is made clear.
Keywords: Cuba; Japan; Cultural Diplomacy; Manga; Anime